2016
DOI: 10.3390/w8080339
|View full text |Cite
|
Sign up to set email alerts
|

Estimated Grass Grazing Removal Rate in a Semiarid Eurasian Steppe Watershed as Influenced by Climate

Abstract: Grazing removal rate of grasses needs to be determined for various climate conditions to address eco-environmental concerns (e.g., desertification) related to steppe grassland degradation. The conventional approach, which requires survey data on animal species and heads as well as grass consumption per individual animal, is too costly and time-consuming to be applied at a watershed scale. The objective of this study was to present a new approach that can be used to estimate grazing removal rate with no require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 34 publications
(43 reference statements)
0
10
0
Order By: Relevance
“…The new algorithms presented in four articles [39,40,44,45,48] provide necessary tools for better modeling effects of grazing on steppe grassland degradation, future climates on sedimentation at watershed scale, micro-topographic features (e.g., puddles) on hydrologic processes, and infiltration on the translational stability of long slopes. In addition, two articles [41,43] found that human activities were the primary reason for runoff reduction, whereas, another article [42] showed that climate variability was the dominant driver for decreasing trend of streamflow.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The new algorithms presented in four articles [39,40,44,45,48] provide necessary tools for better modeling effects of grazing on steppe grassland degradation, future climates on sedimentation at watershed scale, micro-topographic features (e.g., puddles) on hydrologic processes, and infiltration on the translational stability of long slopes. In addition, two articles [41,43] found that human activities were the primary reason for runoff reduction, whereas, another article [42] showed that climate variability was the dominant driver for decreasing trend of streamflow.…”
Section: Discussionmentioning
confidence: 99%
“…The articles cover a wide range of geographic regions across China [39][40][41][42][43][44]46,47,49,50] and the United States of America (USA) [45,48] with contrasting hydro-climate, soil, and vegetation conditions. Thus, the results presented in these articles can have global inferences: the data, analysis/modeling approaches, results, and findings will lay a solid foundation to further our scientific understanding of water-soil-vegetation interactions, ultimately leading to the development of practically effective solutions to sustaining the globe's ecosystem health and productivity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations